BIOCHAR, CHARACTERISTICS AND ITS EFFECTS ON SOIL PROPERTIES AND ENVIRONMENTAL MITIGATION - Abdullah, Rohana (Journal of Islam and Science, 2018)
Biochar (biological charcoal) is a charcoal product produced by heating biomass at temperatures ranging from 400oC-500oC in conditions without oxygen or minimal oxygen (pyrolysis). Biochar has the characteristic of having a high amount of aromatic carbon that is difficult to decompose by microorganisms. The use of biochar in the tropics is very beneficial for maintaining soil fertility and reducing atmospheric pollution with carbon dioxide and methane gases. Effectiveness of biochar depends on the type of biomass and temperature used at pyrolysis. Types of woody biomass produce coarser biochar, while leafy biomass, grasses produce finer biochar. Temperatures exceeding 500oC will produce more ash than biochar. Biochar has biochemical characteristics, aromatic structure and chemical content. Thus it can function to improve physical, chemical and absorbent properties. Aromatic structures are useful in slowing decomposition so that they hold carbon in the soil for long periods. Thus it can slow down the release of carbon and methane into the atmosphere.